Efficacy and safety of ombitasvir/paritaprevir/ritonavir in dialysis patients with genotype 1b chronic hepatitis C. Issue 13 (30th May 2017) - Atsukawa, Masanori; Tsubota, Akihito; Koushima, Yohei; Ikegami, Tadashi; Watanabe, Kouji; Shimada, Noritomo; Sato, Shinichi; Kato, Keizo; Abe, Hiroshi; Okubo, Tomomi; Arai, Taeang; Itokawa, Norio; et al.
Abstract : Aim: From a pharmacokinetic viewpoint, the use of ombitasvir/paritaprevir/ritonavir, one of the standards of care for genotype 1b chronic hepatitis C in Japan, could be possible in patients with impaired renal function. The aim of this study was to assess the efficacy and safety of this combination that have not yet been addressed in patients undergoing dialysis. Methods: A retrospective, multicenter study evaluated the outcome of 12‐week ombitasvir (non‐structural protein [NS]5A inhibitor)/paritaprevir (NS3/4A protease inhibitor)/ritonavir combination therapy for dialysis patients. The primary end‐point was sustained virologic response 12 weeks after therapy (SVR12). Results: The subjects were 31 patients with a median age of 64 years (range, 49–85 years), including 10 cirrhotic patients. All of the 31 patients had an estimated glomerular filtration rate level <15 mL/min/1.73 m 2, defined as end‐stage renal disease (ESRD). Pre‐existing resistance‐associated substitutions at position L31 and Y93 of the NS5A region were detected in 0% and 3.6% (1/28), respectively. The rates of rapid virologic response, end‐of‐treatment response, and SVR12 were 93.5% (29/31), 100% (31/31), and 96.8% (30/31), respectively. The incidence of adverse events was 35.5% (11/31). Of the 11 patients, one discontinued the treatment due to erythema multiforme and thereafter relapsed. The most frequent adverse event was pruritus (6.5%; 2/31). Conclusions: The present study suggests that ombitasvir/paritaprevir/ritonavir combination therapy is effective and safe for genotype 1b chronic hepatitis C patients undergoing dialysis due to ESRD.